Pengaruh Childpose (BALASANA) Terhadap Pengurangan Nyeri Punggung Ibu Hamil Trimester III Di Puskesmas - Wulandari, Ni Ketut Ayu; Adiestiani, Ni Made Egar; Udayani, Ni Putu Mirah Yunita (Jurnal Kebidanan Malakbi, 2024)
Back pain is a frequent and often debilitating symptom experienced by pregnant women during their third trimester. As the fetus grows and the woman's center of gravity shifts forward, the strain on the lower back can increase significantly. This can lead to discomfort, pain, and limited mobility. This study aimed to investigate the efficacy of Balasana (child pose) in alleviating back pain for pregnant women in Kediri Community Health Center 1. Thirty pregnant women experiencing back pain participated in the study. A one-group pretest-posttest design was employed, with pain levels assessed using the Numerical Rating Scale (NRS). Participants performed Balasana as an intervention, followed by a post-intervention pain assessment. The results of the Wilcoxon signed-rank test revealed a significant reduction in back pain levels following the intervention (p = 0.000 < α = 0.05). This suggests that Balasana is an effective strategy for managing back pain in pregnant women. The findings of this study highlight the potential benefits of yoga and mindfulness practices in addressing pregnancy-related discomforts. It is recommended that pregnant women explore various relaxation techniques, including Balasana, to alleviate back pain and promote overall well-being during pregnancy. Balasana has demonstrated effectiveness in reducing back pain among pregnant women. This study underscores the importance of incorporating relaxation techniques into prenatal care to improve the overall comfort and well-being of pregnant individuals.